MPPTM: A Bio-Inspired Approach for Online Path Planning and High-Accuracy Tracking of UAVs - Yi, Xin; Zhu, Anmin; Yang, S. X. (Frontiers in Neurorobotics, 2022)
Path planning and tracking problem of multi-robot system (MRS) has always been a research hotspot and applied in various fields. In this paper, a novel multi-robot path planning and tracking model (MPPTM) is proposed, which can carry out online path planning and tracking problem for multiple mobile robots. It considers many issues during this process, such as collision avoidance, obstacles avoidance, robot fault, and so on. The proposed approach consists of three parts: a neural dynamic path planner, a hyperbolic tangent path optimizer, and an error-driven path tracker. Assisted by Ultra-wideband (UWB) positioning system, the proposed MPPTM is a low-cost solution for online path planning and high-precision tracking of MRS in practical environments. In the proposed MPPTM, the proposed path planner has better time performance, and the proposed path optimizer improves tracking precision. The effectiveness, feasibility, and better performance of the proposed model are demonstrated by real experiments and comparative simulations.